Why Do So Few Preliminary Questions Come From Czechia? - Kunertová Tereza (Wroclaw Review of Law, Administration and Economics)
Although a substantial part of the body of laws of an EU Member State is founded upon European Union law and norms, the number of preliminary questions emanating from courts in the Czech Republic appears to be disproportionately low compared to other similar EU Member States. The aim of this article is to analyse and outline possible reasons for the lack of preliminary questions coming from the Czech Republic. In her analysis, the author identifies three possible factors underpinning the issue. These factors include attitudes towards the EU and a general lack of understanding of the relevance of EU laws and norms; the role of preliminary rulings; and the perception and recognition of courts. An integral part of this analysis is a critical commentary on the shifts in how courts and tribunals are perceived within the meaning of Art. 267 TFEU. Lastly, the author offers guidance to fellow legal professionals and academics for interpreting EU norms.